Protestant Churches, the defense of Human Rights (1976-1983) and the support for Same-Sex Marriage (2010) in Argentina - Jones, Daniel Eduardo (2015)
Religious actors regularly participate in political debates in Latin America. In Argentina, Historical Protestant Churches have been politically involved in several debates since the 1970s. This article compares twoprocesses in which Historical Protestant Churches took part: the defense of Human Rights (1976‐1983) and the support for Same‐Sex Marriage (2010) in Argentina. It is based on a research about the relationships betweenevangelicals, politics and sexuality in Argentina, which focuses on diverse documentary sources (religious and secular press, churches? declarations) and interviews with key informants (especially, evangelical leaders). The article analyzes the performance of these churches because they took an alternative position to most religious actors in Argentina ‐including the Catholic Church and its hierarchy‐ and because they led the ecumenical and interreligious alliances that supported these causes. The main hypothesis is that the performance of these churches in both contexts share significant characteristics that allow us to understand patterns of political participation of religious actors. First, they backed these causes through public statements and activities by their institutional bodies and leaders. Second, they built alliances with other religious and non‐religious actors in order to defend the rights of groups that were politically persecuted or marginalized by the State. By doing so, they led the ecumenical and interreligious space that supported these causes. The recognition of Protestant Churches by social movements and State agencies has increased the visibility of these religious actors in the public sphere and the legitimacy of its political interventions. Without overestimating the influence of the Historical Protestant Churches in Argentina, we believe it is pertinent to point out their roles in the processes described, because in recent decades they have positioned themselves as authorized voices in the political spectrum in favor of the recognition of rights. This place must be considered when analyzing other discussions in Argentina, such as the legalization of abortion.